Transformacja państwowych gospodarstw rolnych w Polsce - Ziętara, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The arguments for ownership changes, legal basis for transformation processes in agriculture as well as directions of state property deployment were presented in the paper. It was revealed that the state owned land has been predominantly leased, then sold. Leasing accounted for 51.2%, and sales respectively for 27.1% of total land at the end of the year 2002. There were 85.3% of dwelling stocks sold. As a result of former state farms restructuring and adjustment processes undergone by new land holders, an employment was radically reduced. It contributed to high unemployment in regions where state farms previously dominated.